Fatigue behaviour of a normal‐strength concrete – number of cycles to failure and strain development. (December 2016) - Hümme, Julian; von der Haar, Christoph; Lohaus, Ludger; Marx, Steffen
Abstract: The fatigue behaviour of concrete is gaining new relevance against the backdrop of continuous developments in concrete construction. Modern types of concrete are achieving ever higher strengths; hence, concrete structures are becoming increasingly attractive for new fields of application such as onshore and offshore wind turbines. The fatigue of concrete has a special relevance for these cyclically loaded structures and knowledge of the number of cycles to failure is no longer sufficient for their design. There are further questions concerning strain and stiffness development and the combination of fatigue loading and maritime environmental conditions which have been investigated with new testing methods at Leibniz Universität Hannover within the scope of the "ProBeton" research project. The first results of this project, which is supported by the Federal Ministry for Economic Affairs and Energy, are presented here.